Multi Akad Dalam Gadai Emas Menurut Erwandi Tarmizi - Ardiansyah Aristama; Erina Pane; A. Kumedi Ja’far (Al Maal: Journal of Islamic Economics and Banking, 2022)
In today's modern era, the Islamic economy in Indonesia is growing very rapidly. This can be seen from the number of financial products that have been implemented by Islamic Financial Institutions, such as gold products with multiple contracts. But of course each of these products must be reviewed first from its halal. This is where the role of the ulama is needed, especially in reviewing and assessing the halalness of LKS products.This study uses a type of library research with a qualitative approach, with the main source of Erwandi Tarmizi's book entitled Harta Haram Muamalat Contemporary. This research is descriptive analytic, where the researcher analyzes and presents the data systematically. The results of the study indicate that Erwandi Tarmizi's opinion on the golden rahn law with multiple contracts should not be carried out because it is not in accordance with the hadith of the Prophet, as well as with the consensus of the scholars and the International Sharia Financial Institution (AAOIFI). The contract is prohibited from closing the usury gap (sadd al-dzari'ah), unless the need is a clearly required cost, in this case the cost is the cost of storing gold that is pawned without taking profit from this fee. The analysis of Islamic law on Erwandi Tarmizi's opinion about the golden rahn law with multiple contracts that it should not be carried out is appropriate, because it is in accordance with the hadith of the Prophet shalallahu 'alaihi wa sallam, the consensus of the scholars and sadd al dzari'ah.